Securities Regulation in an Electronic Age: The Impact of Cognitive Psychology - Robert B. Thompson (Washington University Law Quarterly, 1997)
I think the case can be made that we are moving to a different and richer understanding of what should motivate securities regulation, a change that parallels the emergence of the influence of economics on securities regulation over the last twenty years.
Keywords: Psychology; Electronic trading of securities